The Acknowledgment. Theoretical Difficulties Concerning Self-allocation of Acts - Giebułtowski, Jerzy; Piłat, Robert (Filozofia Chrześcijańska, 2012)
This paper deals with validity conditions of admission to an act. We shall look at admission first as a speech act that has a certain gravity as a legal act. We reconstruct Searle’s success condi- tions for admission and supplement them with particular legal conditions in legal acts of admission and pleas. We focus on the preparatory conditions of admission and we show difficulties involved in fulfilling these conditions.